The Effects of Fiscal Measures During COVID-19 - Deb, Pragyan (IMF Working Papers; Working Paper ;, 2021)
This paper empirically examines the effects of fiscal policy measures during the COVID-19 pandemic, using a novel database of daily fiscal policy announcements-classified by type of fiscal measure-and high-frequency economic indicators for 52 countries from January 1 to December 31, 2020. The results suggest that fiscal policy announcements have been effective in stimulating economic activity, boosting confidence, and reducing unemployment, but their effect varies by type of measure and country characteristics. Emergency lifeline measures (which form the bulk of below-the-line measures) are more effective when containment policies are stringent, providing cashflow support to firms and households. Demand-support measures (which comprise most of above-the-line measures) are more effective when containment measures are relaxed.